2010
DOI: 10.1007/s10237-010-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical study of the mechanical stimuli and tissue differentiation within a CaP scaffold based on micro-CT finite element models

Abstract: The control of the mechanical stimuli transmitted to the cells is critical for the design of functional scaffolds for tissue engineering. The objective of this study was to investigate the dynamics of the mechanical stimuli transmitted to the cells during tissue differentiation in an irregular morphology scaffold under compressive load and perfusion flow. A calcium phosphate-based glass porous scaffold was used. The solid phase and the fluid flow within the pores were modeled as linear elastic solid material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
88
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 23 publications
2
88
0
5
Order By: Relevance
“…In the first case, Finite Element (FE) codes may be used to predict the scaffold properties, starting from the scaffold material and architecture. In the second case, FE codes and/or Computed Fluid Dynamics (CFD) codes are used to compute and/or optimize the mechanical stimuli at the cellular scale generally defined as a combination of flow-induced shear stress and octaheadral shear strain (Sandino and Lacroix, 2011). Indeed, these local mechanical stimuli are known to play a crucial role in the activity of the cells that will be seeded into the scaffold (Ingber, 2006;Butler et al, 2009a), and consequently in the clinical success of the reconstruction strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, Finite Element (FE) codes may be used to predict the scaffold properties, starting from the scaffold material and architecture. In the second case, FE codes and/or Computed Fluid Dynamics (CFD) codes are used to compute and/or optimize the mechanical stimuli at the cellular scale generally defined as a combination of flow-induced shear stress and octaheadral shear strain (Sandino and Lacroix, 2011). Indeed, these local mechanical stimuli are known to play a crucial role in the activity of the cells that will be seeded into the scaffold (Ingber, 2006;Butler et al, 2009a), and consequently in the clinical success of the reconstruction strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Even if they are interrelated, these requirements can be separated into those that aim (1) to restore the function of the native tissue during the rehabilitation period (2) to provide the cells with a suitable micro-environment. In view of satisfying these two types of requirements, the interest of computeraided Tissue Engineering has been largely demonstrated: numerical methods may ease indeed the complexity of the scaffold design stage by enabling to optimize (1) the global properties of scaffolds (Jaecques et al, 2004;Fang et al, 2005;Saito et al, 2010;Chan et al, 2010) (2) the mechanical environment of cells induced by external loading (Sandino et al, 2008;Stops et al, 2010;Sandino and Lacroix, 2011). In the first case, Finite Element (FE) codes may be used to predict the scaffold properties, starting from the scaffold material and architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Cahill et al found that models based on the designed scaffold geometry over-predicted the scaffold stiffness by up to 147% and that surface roughness is a factor that needs to be accounted for 4 . High resolution finite element meshes have been successfully generated from micro-CT scans giving accurate models of the real geometries of both bone tissue engineering scaffolds 6,10,38,49,50,52,57 and native bone tissue 2,29,40,47,51 .Micromechanics approaches to evaluate the mechanical properties of particle-reinforced composites traditionally use idealised microstructures based on particle distribution and are often modelled under periodic boundary conditions 5 . This approach was used by Eshragi et al to determine the bulk mechanical properties of a PCL/hydroxyapatite SLS scaffold 14 .…”
mentioning
confidence: 99%
“…[3][4][5] The correspondingly identified topology has been used to feed various types of numerical analyses being related to elastic properties, 6,7 to permeability, 8,9 or to mechanobiology. 10,11 All these approaches are based on some kind of statistical evaluation of the gray values standardly defining the three-dimensional CT "images", while the deeper physical meaning of these gray values remains somewhat unconsidered. Actually, these voxel-specific gray values, being defined on 8-bit or 16-bit scales, are proportional to the x-ray attenuation coefficient of the material found within the respective voxel.…”
Section: Introductionmentioning
confidence: 99%